FORMULASI NANOPARTIKEL RIBOSOME-INACTIVATING PROTEIN Mirabilis jalapa L. (RIP MJ) TERTARGET MENGGUNAKAN KITOSAN RANTAI PENDEK - PEKTIN TERKONJUGASI ANTIBODI ANTI-EPCAM DAN UJI SITOTOKSIK PADA SEL KANKER PAYUDARA - , Deasy Vanda Pertiwi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ribosome Inactivating Proteins (RIPs) are protein from plants which depurinate ribosomal RNA. RIPs isolated from Mirabilis jalapa L. leaves showed higher cytotoxic effect on malignant cells (T47D and MCF7 cell line) more than on normal mononuclear cells. Chitosan nanoparticles have frequently been used in protein delivery applications. However studies regarding protein delivery using chitosan nanoparticles modification with antibodi specifically targeting EpCAM in tumor tissues are lacking. The aims of this study were to develop RIP MJ entrapped into nanoparticles conjugated antiEpCAM, to characterized nanoparticles of RIP MJ conjugated antiEpCAM, and to study cytotoxic effect on T47D cell line. RIPs loaded chitosan nanoparticles (RIPs CS-Pec NPs) were prepared using low viscous chitosan and pectin as cross-linker with polyelectrolit complex method, then conjugated with antiEpCAM antibodi by carbodiimide reaction. AntiEpCAM conjugated RIPs CS-Pec nanoparticles was then characterized for its entrapment efficiency, particles size, zeta potential, morphology by transmission electron microscope (TEM) and cytotoxic assay on T47D and Vero cell line. The optimal concentration of RIPs